2003
DOI: 10.1210/jc.2002-021758
|View full text |Cite
|
Sign up to set email alerts
|

Follistatin-Related Gene (FLRG) Expression in Human Endometrium: Sex Steroid Hormones Regulate the Expression of FLRG in Cultured Human Endometrial Stromal Cells

Abstract: Follistatin-related gene (FLRG) encodes a novel secreted glycoprotein that is highly homologous to follistatin and binds activins and bone morphogenetic proteins, members of the TGF beta superfamily of growth/differentiation factors. FLRG protein inhibits activin-induced and bone morphogenetic protein-2-induced transcriptional responses in a dose-dependent manner, and its mRNA is abundantly expressed in human placenta, heart, aorta, testis, and adrenal gland. In this study we showed that FLRG mRNA was expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…In their study, FLRG mRNA was weakly detected in the rat pituitary, as shown in LbT2 cells. The finding that FLRG, but not follistatin, expression was increased by activin also provides the possibility of differential regulation of transcription between FLRG and follistatin in pituitary gonadotrope as shown in other tissues such as placenta and skin (Wankell et al 2001, Wang et al 2003. Roles of FLRG in gonadotrope cells need to be further elucidated in the future study.…”
Section: Discussionmentioning
confidence: 83%
“…In their study, FLRG mRNA was weakly detected in the rat pituitary, as shown in LbT2 cells. The finding that FLRG, but not follistatin, expression was increased by activin also provides the possibility of differential regulation of transcription between FLRG and follistatin in pituitary gonadotrope as shown in other tissues such as placenta and skin (Wankell et al 2001, Wang et al 2003. Roles of FLRG in gonadotrope cells need to be further elucidated in the future study.…”
Section: Discussionmentioning
confidence: 83%
“…From the large body of available data, it is apparent that several efforts have been made to understand the functions of single molecules and pathways in endometrium exposed to progesterone (Wang et al 2003, Haendler et al 2004, Kitaya et al 2004. However, the approach of scanning the endometrial transcriptomes during the peri-implantation phase, in the presence and absence of progesterone action, promises to offer not only a holistic view of the role of progesterone in endometrial receptivity, but also the identification of novel molecules that have never been investigated for their role in endometrial receptivity.…”
Section: Introductionmentioning
confidence: 99%
“…It is now well established that activin A is expressed throughout the endometrial cycle in increasing amounts, with the highest levels during the secretory phase (5)(6)(7)(8)(9)(10), and that the human endometrium also expresses activin A receptors (11,12) and both binding proteins, namely follistatin (FS) (7,12) and follistatin-related gene (FLRG) (13,14). Moreover, activin A is secreted by the human endometrium as decidualization progresses, as supported both by in vitro (15,16) and in vivo (7) evidence.…”
mentioning
confidence: 99%